Initial‐to‐Interface Maps for the Heat Equation on Composite Domains. Issue 1 (24th June 2016) - Sheils, Natalie E.; Deconinck, Bernard
Abstract : A map from the initial conditions to the function and its first spatial derivative evaluated at the interface is constructed for the heat equation on finite and infinite domains with n interfaces. The existence of this map allows changing the problem at hand from an interface problem to a boundary value problem which allows for an alternative to the approach of finding a closed‐form solution to the interface problem.